Bone mineral density improves during 2 years of treatment with bisphosphonates in patients with ankylosing spondylitis. Issue 2 (5th July 2020) - Arends, Suzanne; Wink, Freke; Veneberg, Joyce; Bos, Reinhard; van Roon, Eric; van der Veer, Eveline; Maas, Fiona; Spoorenberg, Anneke
Abstract : Aims: To evaluate whether 2 years of treatment with bisphosphonates in combination with calcium/vitamin D supplements has an effect on lumbar spine and hip bone mineral density (BMD) in ankylosing spondylitis (AS) patients starting tumour necrosis factor‐α inhibitors or receiving conventional treatment. Secondly, to explore the development of radiographic vertebral fractures. Methods: Patients from the Groningen Leeuwarden AS cohort receiving bisphosphonates based on clinical indication and available 2‐year follow‐up BMD measurements were included. BMD of lumbar spine (L1–L4) and hip (total proximal femur) were measured using dual‐energy X‐ray absorptiometry. Spinal radiographs (Th4–L4) were scored for vertebral fractures according to the Genant method. Results: In the 20 included patients (median 52 years, 14 males), lumbar spine and hip BMD Z‐scores increased significantly; median from −1.5 (interquartile range [IQR] −2.2 to 0.4) to 0.1 (IQR −1.5 to 1.0); P < .001 and median from −1.0 (IQR −1.6 to −0.7) to −0.8 (IQR −1.2 to 0.0); P = .006 over 2 years, respectively. In patients also treated with tumour necrosis factor‐α inhibitors ( n = 11), lumbar spine and hip BMD increased significantly (median 2‐year change +8.6% [IQR 2.4 to 19.6; P = .009] and +3.6% [IQR 0.7–9.0; P = .007]). In patients on conventional treatment ( n = 9), lumbar spine BMD increased significantly (median 2‐year change +3.6%; IQR 0.7 to 9.0; P = .011) and no improvement was seen in hip BMD (median −0.6%; IQR −3.1 to 5.1; P = .61). Overall, younger AS males with limited spinal radiographic damage showed most improvement in lumbar spine BMD. Four mild radiographic vertebral fractures developed in 3 patients and 1 fracture increased from mild to moderate over 2 years in postmenopausal women and middle‐aged men. Conclusion: This explorative observational cohort study in AS showed that 2 years of treatment with bisphosphonates in combination with calcium/vitamin D supplements significantly improves lumbar spine BMD. Mild radiographic vertebral fractures still occurred.